1972
DOI: 10.1002/qj.49709841507
|View full text |Cite
|
Sign up to set email alerts
|

Observations of lee waves by high‐power radar

Abstract: A very high-sensitivity 107 mm radar has been brought into operation for meteorological studies of airflow within the optically clear (or cloudy) atmosphere. One application of this radar has been to observe the detailed three-dimensional structure of lee waves, using backscatter from both refractive index inhomogeneities and cirrus 'clouds' as means of tracing the pattern of airflow. This paper presents case studies showing how the radar has revealed the structure of lee waves downwind from the Welsh mountain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…Additional evidence for the existence of clear-air radar layers associated with large variations of refractive index has been given by Saxton et al (1964), Hardy et al (1966), and Kropfli et al (1968). Multiple stratifications have been reported recently by Ottersten (1969a), Katz (1969), Crane (1970), Kropfti (1971) and Starr and Browning (1972). The scattering layers may be quite shallow, perhaps only a few meters thick as reported by , or they may be of the order of 1 km in depth.…”
Section: Backscatteringmentioning
confidence: 75%
See 2 more Smart Citations
“…Additional evidence for the existence of clear-air radar layers associated with large variations of refractive index has been given by Saxton et al (1964), Hardy et al (1966), and Kropfli et al (1968). Multiple stratifications have been reported recently by Ottersten (1969a), Katz (1969), Crane (1970), Kropfti (1971) and Starr and Browning (1972). The scattering layers may be quite shallow, perhaps only a few meters thick as reported by , or they may be of the order of 1 km in depth.…”
Section: Backscatteringmentioning
confidence: 75%
“…Both the short and long waves maintained fixed positions with respect to the ground in the lee of the Welsh mountains. Reed and Hardy (1972) describe some long waves which, in contrast to the stationary lee waves observed by Starr and Browning (1972), were embedded within the mean flow. A portion of one of the waves is shown in Figure 14.…”
Section: Internal Gravity Wavesmentioning
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, observational evidence readily demonstrates that trapped waves display notable nonstationary behavior (Vergeiner and Lilly 1970;Ralph et al 1992;Worthington and Thomas 1996), with significant changes sometimes occurring on time scales of less than 1 h (Ralph et al 1997). Temporal changes in amplitude (Starr and Browning 1972;Brown 1983), downstream position and extent (Lindsay 1962), and horizontal wavelength (Holmboe and Klieforth 1957;Queney et al 1960;Smith 1976;Mitchell et al 1990;Ralph et al 1997) have all been observed. In particular, in an analysis of 24 observed events, Ralph et al (1997) found that the resonant wavelength of trapped waves gradually increased at an average rate of 9% h 21 .…”
Section: Introductionmentioning
confidence: 97%
“…Mountain waves can modify downwind convection (Hosler et al, 1963;Booker, 1963;Starr and Browning, 1972;Winstead et al, 2002), however mountain-wave clouds can also occur above convection (Pigot and Hill, 1939;Sinha, 1966;Müller, 1983) covering the mountains, as if the wave source region could be higher than the mountain surface. Sea-breeze convection could also form an "additional effective mountain" (Kozhevnikov et al, 1986).…”
Section: Introductionmentioning
confidence: 99%